Day‐case catheterless and drainless minimal‐access pyeloplasty in adults: A single‐center experience of 13 years. (22nd February 2021) - Murali, Vinodh; Donati‐Bourne, Jack; Thomas, Megan; Luscombe, Christopher; Golash, Anurag; Fernando, Herman
Abstract : Objectives: To analyze our practice of drainless and catheterless day‐case minimal‐access pyeloplasty with regard to feasibility, safety and long‐term outcomes. Methods: Patients undergoing minimal‐access pyeloplasty (laparoscopic, with or without robotic assistance) in a single center between 2007 and 2020 were included in this retrospective observational study. Patient demographics and the success rate of day‐case discharge along with postoperative outcomes were analyzed. Results: A total of 129 patients underwent minimal‐access pyeloplasty in this time period, of whom 116 met the inclusion criteria. The mean patient age was 48 years. A total of 65% of the patients ( n = 75) were discharged on the same day and 88% ( n = 101) were discharged within 23 h of surgery. Of the 14 patients with a hospital stay of >24 h, pain was the most common reason (60%) for delayed discharge. The overall subjective (pain‐free status) and objective (unobstructed drainage) success rates were 91% and 86%, respectively. Conclusion: This study demonstrates that routine drains or urethral catheters are not necessary in minimal‐access pyeloplasty, and their omission could facilitate early recovery and day‐case discharge without compromising long‐term surgical outcomes. Large randomized controlled studies are required to prospectively evaluate outcomes.